Effects of Emodin on CCl4 Induced Liver Fibrosis in Mice Model - Mohannad Falah Hassan (Journal of Global Pharma Technology, 2020)
Many compounds demonstrated an anti-fibrotic activity, but none have been used in the clinics. The current study aims to assess the in-vivo emodin anti-fibrotic activity in liver fibrosis. Thirty-two mice were divided into four groups; the first group is composed of eight healthy mice to be a negative control group, while the remaining twenty-four mice had received intraperitoneal carbon tetrachloride 1ml/kg twice weekly for six weeks. Then, eight of these mice were sacrificed to be a positive control group, while the remaining sixteen mice were divided into two groups; one received six intraperitoneal doses every other day of emodin 40 mg/kg and the other received silymarin 20 mg/kg. Mice livers have taken and examined histopathologically to confirm the diagnosis of liver fibrosis and to assess the antifibrotic effects of emodin, then immunohistochemical evaluation was done for collagen III and Interleukin-4 secretion. Statistics used are ANOVA test followed by Tukey’s post HOC analysis. Emodin reduces fibrosis significantly in histopathologic sections, collagen content and Interleukin-4 content (in which p˂0.0001 was significant). There is no significant difference between emodin and silymarin in lowering fibrosis grade (p=0.1411), collagen III level (p=0.958729), and interleukin-4 level (p=0.144028). Emodin anti-fibrotic effects is related to lowering nuclear factor-ĸB leading to IL-4 lowering, decrease of epithelial mesenchymal transition by increasing E-cadherin, suppression of TGF-ß1 Smad signaling, Up-regulation of metastasis‑ associated gene 3, inhibits the Toll-like receptor-4 (TLR-4) pathway, and blocking the migration and proliferation of HSCs induced by platelet derived growth factor. Emodins have anti-fibrotic activity comparable to that of silymarin and can alleviate liver cirrhosis.Keywords: Liver fibrosis, Collagen III, Emodin, Interleukin-4, Silymarin.